Reperfusion Therapies of Acute Ischemic Stroke: Potentials and Failures - Tsivgoulis, Georgios; Katsanos, Aristeidis H.; Alexandrov, Andrei V. (Frontiers in Neurology, 2014)
Over the past twenty years clinical research has focused on the development of reperfusion therapies for acute ischemic stroke (AIS), which include the use of systemic intravenous thrombolytics (alteplase, desmoteplase or tenecteplase), the augmentation of systemic intravenous recanalization with ultrasound, the bridging of intravenous with intra-arterial thrombolysis, the use of multi-modal approaches to reperfusion including thrombectomy and thromboaspiration with different available retrievers. Clinical trials testing these acute reperfusion therapies provided novel insight regarding the comparative safety and efficacy, but also raised new questions and further uncertainty on the field. Intravenous alteplase (tPA) remains the fastest and easiest way to initiate acute stroke reperfusion treatment, and should continue to be the first-line treatment for patients with AIS within 4.5 hours from onset. The use of tenecteplase instead of tPA and the augmentation of systemic thrombolysis with ultrasound are both novel therapeutical modalities that may emerge as significant options in AIS treatment. Endovascular treatments for AIS are rapidly evolving due to technological advances in catheter-based interventions and are currently emphasizing speed in order to result in timely restoration of perfusion of still-salvageable, infracted brain tissue, since delayed recanalization of proximal intracranial occlusions has not been associated with improved clinical outcomes. Comprehensive imaging protocols in AIS may enable better patient selection for endovascular interventions and for testing multi-modal combinatory strategies.